(untitled) (Global Journal of Science Frontier Research, 2016)
Dialkylated methylimidazolium halide salts are a current research topic. The 1octanol/water partition coeffcient for these salts has come to signify the tendency of a charged organic molecule to cross a biological membrane, be sequested in soil, and indicate the lethal dose of the chemical. The purpose of this work is to add to existing data for the 1-octanol/water partition coeffcient for these salts. The novelty of this work is that dialkylated methylimidazolium salts are investigated.